Coblation intracapsular tonsillectomy: A cohort study of NHS practice in England using Hospital Episode Statistics. (22nd March 2022) - Powell, Steven; Tweedie, Daniel J.; Jonas, Nicolaas E.; Bateman, Neil D.; Keltie, Kim; Sims, Andrew J.
Abstract: Objectives: To identify paediatric intracapsular Coblation tonsillectomy procedures from routine administrative data in England, and determine their safety. Design: Retrospective observational cohort study of four ENT centres using routine data from Hospital Episode Statistics (HES). Setting: Acute NHS trusts in England conducting exclusively intracapsular Coblation tonsillectomy. Participants: Children (≤16 years old) undergoing bilateral intracapsular Coblation tonsillectomy. Main outcome measures: Number of procedures, readmissions for pain, readmissions for bleeding and requirement for additional surgery for regrowth. Results: A total of 5525 procedures were identified. The median patient age was 4 (IQR 2–5). In‐hospital complications occurred in 1%, with 0.1% returning to theatre for arrest of primary tonsil bleeding. Almost half of the procedures were conducted as a day‐case (44%), with only a small proportion staying in hospital more than one night (7%). Within 28 days, 1.2% of patients were readmitted with bleeding, 0.7% with infection and 0.3% with pain; 0.2% of patients required return to theatre for control of secondary haemorrhage. Longitudinal follow‐up has found that revision tonsil surgery is 0.3% at 1 year ( n  = 4498), 1.1% at 2 years ( n  = 2938), 1.7% at 3 years ( n  = 1781), 1.9% at 4 years ( n  = 905) and 2.2% at 5 years ( n  = 305). Conclusions: Intracapsular coblation tonsillectomy safety outcomes in this study show primary and secondary bleeding rates and emergency return to theatre rates are lower than all tonsillectomy techniques reported in the National Prospective Tonsillectomy Audit and also lower than previously published Hospital Episode Statistics analysis of tonsillectomy procedures.